Adsorption Potential of Schizophyllum commune White Rot Fungus for Degradation of Reactive Dye and Condition Optimization: A Thermodynamic and Kinetic Study. (2nd February 2023) - Raees, Alia; Bhatti, Haq Nawaz; Alshehri, Sameer; Aslam, Farheen; Al-Fawzan, Foziah F.; Alissa, Siham A.; Iqbal, Munawar; Nazir, Arif
Abstract : The pollution due to dyes from textile sector is one of the major issues faced worldwide. This study was focused on the removal of the reactive dye, Drimaren Turquoise CL-B using Schizophyllum commune, a white rot fungus (WRF) keeping in mind the current environmental conditions. Different parameters like pH, sources of carbon & nitrogen, temperature, concentration of dye and C/N ratio were used to investigate their effect on the process. Maximum dye removal of 95.45% was obtained at pH 4.5, temperature 35°C, inoculum size 3 mL, veratryl alcohol (mediator), glucose (carbon source) and ammonium nitrate (nitrogen source). The enzyme activity was determined by employing enzyme assay. Laccase and Lignin peroxidase (LiP) activity was low while Manganese peroxidase (MnP) activity was highest. Maximum bio-sorption was achieved at pH 1 and 313 K. The pseudo-2 nd -order kinetic model & Freundlich isotherm was best suited for the process of removal of dye. From these data, it is concluded that white rot fungus could possibly be the excellent biomaterial for elimination of synthetic dyes from wastewater.